Manipulating Gene Expression in Projection‐Specific Neuronal Populations Using Combinatorial Viral Approaches. Issue 1 (28th March 2018) - Gore, Bryan B.; Soden, Marta E.; Zweifel, Larry S.
Abstract: The mammalian brain contains tremendous structural and genetic complexity that is vital for its function. The elucidation of gene expression profiles in the brain, coupled with the development of large‐scale connectivity maps and emerging viral vector–based approaches for target‐selective gene manipulation, now allows for detailed dissection of gene‐circuit interfaces. This protocol details how to perform combinatorial viral injections to manipulate gene expression in subsets of neurons interconnecting two brain regions. This method uses stereotaxic injection of a retrograde transducing CAV2‐Cre virus into one brain region, combined with injection of a locally transducing Cre‐dependent AAV virus into another brain region. This technique is widely applicable to the genetic dissection of neural circuitry, as it enables selective expression of candidate genes, dominant‐negatives, fluorescent reporters, or genetic tools within heterogeneous populations of neurons, based upon their projection targets. Curr. Protoc. Neurosci . 65:4.35.1‐4.35.20. © 2013 by John Wiley & Sons, Inc.